Prospective study in a porcine model of sarcoptes scabiei indicates the association of Th2 and Th17 pathways with the clinical severity of scabies. - Kate E Mounsey; Hugh C Murray; Helle Bielefeldt-Ohmann; Cielo Pasay; Deborah C Holt; Bart J Currie; Shelley F Walton; James S McCarthy (Public Library of Science (PLoS), 2015)
BACKGROUND:Understanding of scabies immunopathology has been hampered by the inability to undertake longitudinal studies in humans. Pigs are a useful animal model for scabies, and show clinical and immunologic changes similar to those in humans. Crusted scabies can be readily established in pigs by treatment with the glucocorticoid dexamethasone (Dex). METHODOLOGY/ PRINCIPAL FINDINGS:Prospective study of 24 pigs in four groups: a) Scabies+/Dex+, b) Scabies+/Dex-, c) Scabies-/Dex+ and d) Scabies-/Dex-. Clinical symptoms were monitored. Histological profiling and transcriptional analysis of skin biopsies was undertaken to compare changes in cell infiltrates and representative cytokines. A range of clinical responses to Sarcoptes scabiei were observed in Dex treated and non-immunosuppressed pigs. An association was confirmed between disease severity and transcription of the Th2 cytokines IL-4 and IL-13, and up-regulation of the Th17 cytokines IL-17 and IL-23 in pigs with crusted scabies. Immunohistochemistry revealed marked infiltration of lymphocytes and mast cells, and strong staining for IL-17. CONCLUSIONS/ SIGNIFICANCE:While an allergic Th2 type response to scabies has been previously described, these results suggest that IL-17 related pathways may also contribute to immunopathology of crusted scabies. This may lead to new strategies to protect vulnerable subjects from contracting recurrent crusted scabies.